Sherman H. Eoff. The Novels of Pérez Galdós. The concept of life as dynamic process. Washington University Studies, Saint Louis, 1954; 178 pp. / Walter T. Pattison, Benito Pérez Galdós and the creative process. University of Minnesota Press, Minneapolis, 1954; 140 pp. - Blanco Aguinaga, Carlos (El Colegio de México, 1955)
Se reseñaron: S. H. Eoff, The Novels of Pérez Galdós. The concept of life as dynamic process y W. T. Pattison, Benito Pérez Galdós and the creative process.